Single cell proteogenomic sequencing identifies a relapse‐fated AML subclone carrying FLT3‐ITD with CN‐LOH at chr13q. Issue 2 (24th February 2022) - Kim, TaeHyung; Lee, Hyewon; Capo‐Chichi, Jose‐Mario; Chang, Myung Hee; Yoo, Young Seok; Basi, Gurbaksh; Ketela, Troy; Smith, Adam C.; Tierens, Anne; Zhang, Zhaolei; Minden, Mark D.; Kim, Dennis Dong Hwan
Abstract: Internal tandem duplication of the Feline McDonough Sarcoma (FMS)‐like tyrosine kinase 3 ( FLT3 ‐ITD) is one of the most clinically relevant mutations in acute myeloid leukemia (AML), with a high FLT3 ‐ITD allelic ratio (AR) (≥0.5) being strongly associated with poor prognosis. FLT3 ‐ITDs are heterogeneous, varying in size and location, with some patients having multiple FLT3 ‐ITDs. Bulk cell‐based approaches are limited in their ability to reveal the clonal structure in such cases. Using single‐cell proteogenomic sequencing (ScPGseq), we attempted to identify a relapse‐fated subclone in an AML case with mutations in WT1, NPM1, and FLT3 tyrosine kinase domain and two FLT3 ‐ITDs (21 bp and 39 bp) (low AR) at presentation, then relapsed only with WT1 and NPM1 mutations and one FLT3 ‐ITD (high AR). This relapse‐fated subclone at presentation (∼2.1% of sequenced cells) was characterized by the presence of a homozygous 21 bp FLT3 ‐ITD resulting from copy neutral loss of heterozygosity (CN‐LOH) of chr13q and an aberrant, immature myeloid cell surface signature, contrast to the cell surface phenotype at presentation. In contrast to results from multicolor flow‐cytometry, ScPGseq not only enabled the early detection of rare relapse‐fated subclone showing immature myeloid signature but also highlighted the presence of homozygous 21 bp FLT3 ‐ITDs in the clone at presentation.